A BVAR Approach to the Impact of Policy Uncertainty on International Trade and Investment. Issue 3 (December 2018) - Dhannur, Vijaykumar; John, Ashwin R.
This article investigates the impact of economic policy uncertainty (EPU) on foreign trade and investment into India relative to other macroeconomic factors with reference to the Indian pharmaceutical industry. It employs the Bayesian vector autoregression (BVAR) approach to construct a model and then study the said impact by the impulse response function (IRF) analysis. In a Bayesian procedure, the parameters are treated as random variables and their posterior distribution is estimated via the imposition of prior beliefs on their distribution, which makes the analysis more robust when combined with vector autoregression. The IRF analysis shows no substantial protracted impact of policy uncertainty, inflation and interest rates on the pharma exports. Also, inflation seems to have a more pronounced impact on FDI as compared to the interest rate changes contemporaneously.